Health system's barriers hindering implementation of public-private partnership policy in the health sector at district level: A case study of partnership for improved reproductive and child health services provision in Bagamoyo district, Tanzania - Kamugumya, Denice Cyprian (Department of Public Health and Family Medicine, 2015)
The role of the private sector in improving health systems performance in lower to middle income countries is increasingly gaining more recognition. Public-private partnership (PPP) has been suggested as a tool, to assist governments fulfil their responsibilities in the efficient delivery of health services. In Tanzania, although the idea of PPP has existed for many years in the health sector, there has been limited coordination, especially at a district level - which has contributed to limited health gains or systems strengthening obviously seen as a result of PPP. In 2009 a formal PPP policy was introduced in Tanzania, which directs the appropriate allocation of resources, and describes risk and rewards that can be achieved by building on the expertise of each partner. The Health Sector Strategic Plan III (2009-2015) further emphasises the need for service level agreements (SLAs), which are seen as an important indicator of improved PPP. This case study that draws on the decision-space framework, was conducted in the Bagamoyo district of Tanzania, and employed in-depth interviews, document reviews, and observations methods. The study findings reveal several forms of informal partnerships between the local government and non-state actors. The lack of SLAs for facilities that receive subsides from the government is argued to contribute to inappropriate distribution of risk and reward leading to moral hazards. This is evidenced by non-state actors who pursue their own interests, diverting from public social goals. Furthermore, findings highlight weak capacity of governing bodies to exercise oversights and sanctions, which is acerbated by weak accountability linkages and power differences. Moreover, restricted flexibility in spending is seen to deter prompt actions to address evolving population needs, given limited local fiscal space. It is concluded that effective PPP policy implementation at a local level depends on the capacity of local government officials to make choices that would embrace relational elements dynamics in strategic plans. Disempowered Council Health Services Board in relation to engaging non-state actors is shown to impede PPP initiatives that are conceptualized at local and national levels. This study highlights a need to consider initiatives that would foster new social contracts with non-state actors at the local level and in return build a people-centred district health system. This study is intended to improve knowledge on health systems policy interventions, strengthen future policy implementation at the sub-national level, and strengthen the district health systems as a result of PPP in a country with similar contextual elements.